Effective agricultural information delivery system-an action research among farmers - Nazreen Hassan S (Department of Agricultural Extension, College of Agriculture, 2008)
Extension providers and client expectations include superior information accessing and dissemination, ongoing farmer-extension-research communications and marketing. AgIDS offer tremendous potential for accelerating development. They are transforming our lives, creating wealth and impacting every facet of human endeavor. Agricultural marketing requires connectivity between the market and exporters, growers, traders, industry consumers, through wide area network of national and international linkages in order to provide day-to-day information with regard to commodity arrivals and prevailing rates etc. this study was carried out with the objective of bringing out the underlying facts in the Information Communication technology available to the benefit of the farmers. Thiruvananthapuram district has been purposively selected for the study because this is the only district in Kerala having information kiosks being operated in the Krishibhavans. From the ten Krishibhavans three Krishibhavans were selected based on the maximum numbers of users of this ICT facility based on the records available in the Krishibhavans. The respondents were selected by random sampling method. 60 user farmers and 30 non-user farmers from each panchayat were selected and they formed the respondents of this study. A total of 270 farmers were contacted for the study. From a review of related literature and discussion with experts a comprehensive list of variables were selected. The dependent variables included attributes of ICT, Communication behaviour, information need and skill requirement. Majority of the farmers came under middle age group. Majority of the farmer in both the categories were found to be marginal farmers. Mostly the users were in a better socio economic group. The Extension Service must be able to provide information that makes a difference. ICTs are tools that help build human network, increase public awareness and provide access to information and knowledge for the use of people. They include Telephone, Fax, GIS, Radio, Television, Print, Internet, Video, Audio, Computer and technologies on the drawing boards. Possession of ICT tools by users was found to be higher than the nonusers except for farm magazines where the nonusers out-numbered the users. The mean of the socio technical variables was found to be the maximum for physical compatibility and desirability in the case of users. This was followed by social acceptability and simplicity. This was followed by physical compatibility and social acceptability. In both the cases user education had the minimum score. So this area needs more attention. Majority of farmers in both the categories perceived efficiency of ICT as ‘saving time and money in interacting’ and has ‘all information the farmer wants’ in the nonuser category. This was followed by one stop shop information by the users and supports marketing in the case of non users. There existed significant relation ship between the dependent variables. Also significant relationship was observed in the relationship that existed between some independent variables and dependent variables. A majority of the users claim that they slightly agree to the fact that their productivity has increased compared to the previous year. Analysis of variance showed a comparison between the user group and the non user group. It was found that the user group was higher in the case of all dependent variables. But in the case of information need it was found to be almost similar. A need assessment can help Extension educators to decide whether an extension program should be improved and how the services should be better delivered. The farmers needed information on agriculture such as market rates, bio pesticides, bio fertilizers. These areas ranked top in their information needs. This was followed by organic farming, plant protection and cropping practices. The skill requirement of the non-users farmers was more than the user farmers.